Sustainable Financial Literacy Policy in Breaking the Chain of Household Debts and Receivables - Fadli, Ahmad; Fawaid, Yazidul (OECONOMICUS Journal of Economics, 2023)
This riset to explore the practices of debt and receivables that occur in households. Secondly, to formulate a sustainable financial literacy policy through digital applications and cooperative innovations, transforming the concept of conventional "lump sum" banks into Sharia-based installment banks. This work utilizes a literature review and netnography as the primary research methods. These approaches are employed to gather data from various social media conversations and observe phenomena related to debt and receivables transactions in society. Data is obtained through literature and documentary studies. The data analysis employs an interpretive approach to interpret the data related to policies in conducting sustainable financial literacy. In Indonesian households, there are various types of debt and receivables practices. These include debt to financial institutions such as banks and nonbank entities, debt through conventional "lump sum" banks, debt to loan sharks, debt through online applications (fintech platforms), debt to neighbors, debt through cooperatives, and debt acquired through rotating savings and credit associations (arisan). Various debt models exist within Indonesian households. Addressing these issues is possible through the implementation of applicationbased financial literacy policies, thereby preventing accumulating debts. The application-based financial literacy policy is employed to prevent debt and receivables practices from exceeding the household's capacity. If debt behavior can be controlled, it will contribute to the realization of sustainable financial models. Previous research has not presented relevant and application-based financial literacy policies. Thus, this research is both relevant and accurate in addressing this gap.